Dakwah Management in Technical Higher Education: Integrating Islamic Communication Principles into Engineering University Curricula - Hasanov Elnur Latif Oglu (Fakultas Dakwah UIN KHAS Jember, 2026)
Technical and engineering disciplines operate within an increasingly globalised environment that requires cross-border collaboration grounded in shared values and ethical communication. In this context, dakwah—understood as purposeful Islamic communication—provides a relevant framework for conveying knowledge with integrity, clarity, and moral responsibility. However, many engineering students in Islamic or Muslim-majority universities still face challenges in integrating Islamic communication principles into their academic and professional development. Therefore, this study aims to examine the role of dakwah-based communication principles in enhancing the professional readiness of engineering students and to identify the key challenges in their implementation. This study employs a library research approach, drawing on a wide range of scholarly sources, including academic books, peer-reviewed journal articles, and relevant theoretical frameworks related to Islamic communication, dakwah management, and engineering education. The data were analyzed using qualitative content analysis to identify recurring themes, conceptual relationships, and theoretical insights regarding the integration of Islamic values into professional communication. The findings reveal that the integration of dakwah-based communication principles significantly contributes to the development of ethical awareness, effective communication skills, and global professional competitiveness among engineering students. Furthermore, the study highlights several critical challenges, including limited institutional support, insufficient pedagogical integration, and gaps in students’ ability to articulate technical knowledge within Islamic ethical frameworks. The study concludes that embedding dakwah management into engineering curricula is essential for fostering graduates who are not only technically competent but also ethically grounded and globally competitive.